Reflections on Consumer Protection in the WAEMU zone within its perspective of community economic integration : Comparative study with European (French) law - (:unkn) unknown (My University, 2016)
For a number of years, WAEMU member states have been engaged in a major project of economic liberalization followed by an ambition for an economic integration. This makes consumerist national legislative projects difficult. This study questions whether these ambitions for economic integration take into account the interests of consumers and whether we need an effective consumer protection in the common market. How could this economic liberalism be reconciled with an effective consumer protection within the common market? In other words, would a divergence between the various provisions of the Member States be harmful to consumers? Finally, can we actually speak about a real West-African consumer protection law? Throughout this study it will be demonstrated that community consumer protection exists, but it is sectoral. However, the areas left “vacant” by Community Law are implicitly governed by different national embryonic and mostly identical provisions. Hence the risk of legal uncertainty and the need for the OHADA project on contract law as a perspective within the framework of consumer protection in WAEMU and within the common market.
Keywords: African Research